Paracoccidioimycosis and white individuals: Susceptibility and biogeographic aspects in an important endemic area in Brazil - Zeminian de Oliveira, Luciana Bonome [UNESP]; Della Coletta, Amanda Manoel [UNESP]; Gardizani, Taiane Priscila [UNESP]; Barrozo, Ligia Vizeu; Miot, Hélio Amante [UNESP]; De Faveri, Julio [UNESP]; Dias-Melicio, Luciane Alarcão [UNESP] (Public Library of Science (PLoS), 2021)
Paracoccidioidomycosis (PCM) is a neglected mycosis most commonly occurring in Latin America. The etiologic agents are thermo dimorphic fungi of the genus Paracoccidioides, and cause an important granulomatous response in affected tissues. The Botucatu Medical School, from São Paulo State University (UNESP), is a PCM study pole, located in São Paulo State Midwest region, which is classified as a hyperendemic area in the Southeast region in Brazil. This study aimed to perform a retrospective epidemiological, geographical, and clinical analysis by the information available in medical records. It was listed as socio-demographic data along with clinical characteristics from patients diagnosed and treated during a 10-year period in Botucatu, totaling 177 patients with Paracoccidioidomycosis con-firmed by the histopathological test. It was observed that the main clinical presentation was the chronic type (76,3%), most commonly identified in white male individuals over the age of 29 years old, smokers, and alcoholics, providing evidences for the first time that white individuals were more affected by the disease, in comparison to non-white individuals that may be more resistant to infection. This data opens new avenues for study within ancestry, resis-tance and susceptibility in paracoccidioidomycosis.